Meningkatkan Hasil Belajar Pendidikan Pancasila dan Kewarganegaraan (PPKn) Tema 8 Peristiwa Alam pada Peserta Didik Kelas I B SD Negeri Kasreman Melalui Media Gambar Seri di Semester II Tahun Pelajaran 2018/2019 - Saptaningrum Saptaningrum (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
The type of this research is a Class Action Research (CAR) with the purpose to analyze the Civic Education learning outcome on the Eighth Chapter about Natural Phenomena of the students of Class I B the Elementary School of Kasreman with the media of serial pictures on the Second Semester of the 2018/2019 year academic.The subjects of this research are the students of Class I B the Elementary School of Kasreman on the Second Semester of the 2018/2019 year academic as much as twenty three children; consist of ten boys and thirteen girls. The data resources of this research are relating with learning activities and learning outcomes. Techniques of collecting data of this research are non test technique and test technique. Technique of analyzing data of this research is comparative description. The procedure of this research is the Kemmis and Mc Taggart’s cycle model. The results of this research are 1) the Civic Education learning on the Eighth Chapter about Natural Phenomena with the media of serial pictures is a group task, 2) the Civic Education learning on the Eighth Chapter about Natural Phenomena with the media of serial pictures has function as a concrete, interesting and effective learning media, 3) the Civic Education learning on the Eighth Chapter about Natural Phenomena with the media of serial pictures is improving the learning activities in actively discussing, cooperating collaboration, actively answering the questions form the teacher and other students and actively asking the questions and 4) the Civic Education learning outcome on the Eighth Chapter about Natural Phenomena with the media of serial pictures is improving, from not good category into good one. The learning outcomes on the Early Condition are 63,91 for the average and 52,17% for the completeness. The learning outcomes on the First Cycle are 76,08 for the average and 73,91% for the completeness. The learning outcomes on the Second Cycle are 86,65 for the average and 91,3% for the completeness.